PARTISIPASI DIGITAL MASYARAKAT DALAM PELESTARIAN TRADISI ABDA’U SEBAGAI PARIWISATA BERBASIS KOMUNITAS - Ririn Dwi Iriyanti Tatuhey; Hayat Hayat; Hirshi Anadza (Ikatan Dosen Menulis, 2026)
This study aims to analyze community digital participation in preserving the Abda’u Tradition as community-based tourism in Tulehu Village, Central Maluku Regency. The research focuses on how local communities, particularly young people, utilize digital media to support cultural documentation, communication, promotion, and education while maintaining customary values and digital ethics. This study employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Research informants include traditional leaders, the Abda’u Tradition organizing committee, village government representatives, and community members directly involved in the tradition. Data were analyzed thematically based on Digital Citizenship indicators, including digital access, digital communication, digital literacy, digital ethics, and digital rights and responsibilities. The findings indicate that community digital participation is participatory, collective, and selective, with youth serving as the main driving force. Digital media are used to disseminate information and document cultural activities while respecting customary norms, particularly in sacred ritual processes. However, challenges remain, including limited equipment, technical skills, and institutional support, which need to be addressed to optimize sustainable cultural preservation.